Peli1 deletion in macrophages attenuates myocardial ischemia/reperfusion injury by suppressing M1 polarization. Issue 2 (16th January 2023) - Chen, Hao; Hou, Yuxing; Zhai, Yali; Yang, Jie; Que, Linli; Liu, Jichun; Lu, Linming; Ha, Tuanzhu; Li, Chuanfu; Xu, Yong; Li, Jiantao; Li, Yuehua
Abstract: The polarization of macrophages to the M1 or M2 phenotype has a pivotal role in inflammatory response following myocardial ischemia/reperfusion injury. Peli1, an E3 ubiquitin ligase, is closely associated with inflammation and autoimmunity as an important regulatory protein in the Toll-like receptor signaling pathway. We aimed to explore the function of Peli1 in macrophage polarization under myocardial ischemia/reperfusion injury and elucidate the possible mechanisms. We show here that Peli1 is upregulated in peripheral blood mononuclear cells from patients with myocardial ischemia/reperfusion, which is correlated with myocardial injury and cardiac dysfunction. We also found that the proportion of M1 macrophages was reduced and myocardial infarct size was decreased, paralleling improvement of cardiac function in mice with Peli1 deletion in hematopoietic cells or macrophages. Macrophage Peli1 deletion lessened M1 polarization and reduced the migratory ability in vitro. Mechanistically, Peli1 contributed to M1 polarization by promoting K63-linked ubiquitination and nuclear translocation of IRF5. Moreover, Peli1 deficiency in macrophages reduced the apoptosis of cardiomyocytes in vivo and in vitro. Together, our study demonstrates that Peli1 deficiency in macrophages suppresses macrophage M1 polarization and alleviates myocardial ischemia/reperfusion injury by inhibiting the nuclear translocation of IRF5, which may serve as a potential intervention target for myocardial ischemia/reperfusion injury. Abstract : Peli1 regulates macrophage M1 polarization through the ubiquitination of IRF5 and subsequently promotes cardiomyocyte apoptosis under myocardial ischemia/reperfusion.